2017
DOI: 10.1186/s12936-017-2012-8
|View full text |Cite
|
Sign up to set email alerts
|

Does mosquito mass-rearing produce an inferior mosquito?

Abstract: BackgroundThe success of the sterile insect technique depends, among other things, on continuous releases of sexually competitive sterile males within the target area. Several factors (including high rearing density and physical manipulation, such as larvae and pupae separation) can influence the quality of males produced in mass-rearing facilities. The different steps in mass production in the laboratory may modify the behaviour of mosquitoes, directly or through loss of natural characters as a result of adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Water was added to each tray 24 h before the addition of the eggs to allow the temperature of the water to acclimatize to that of the ambient air temperature. Larvae were fed daily on a 1% (wt/vol) diet developed by the IAEA and described in [17], following the feeding regime described in the guidelines for mass rearing Anopheles mosquitoes [18]. Larvae were maintained in a large climate-controlled room (88 m 2 ) with temperature and humidity maintained at 30 ± 1 °C, 70 ± 10% RH, respectively.…”
Section: Mosquito Colony Source and Mass Rearing Proceduresmentioning
confidence: 99%
“…Water was added to each tray 24 h before the addition of the eggs to allow the temperature of the water to acclimatize to that of the ambient air temperature. Larvae were fed daily on a 1% (wt/vol) diet developed by the IAEA and described in [17], following the feeding regime described in the guidelines for mass rearing Anopheles mosquitoes [18]. Larvae were maintained in a large climate-controlled room (88 m 2 ) with temperature and humidity maintained at 30 ± 1 °C, 70 ± 10% RH, respectively.…”
Section: Mosquito Colony Source and Mass Rearing Proceduresmentioning
confidence: 99%
“…The translation from benchtop to industrial scale is not necessarily linear, thus moving from benchtop results to industrial production, without first testing results at the industrial level, is not acceptable. Many studies are related to the possible modifications caused by scaling from laboratory to mass rearing 28,29 . For example, it was observed that mass rearing system positively influenced number of progeny (higher) and developmental time (shorter) of Cylas formicarius elegantulus (Coleoptera: Brentidae) 30 and weight and size (both higher) of Aedes aegypti (Diptera: Culicidae) and Aedes albopictus (Diptera: Culicidae) eggs 31 .…”
mentioning
confidence: 99%
“…Following the egg quantification method described in Maiga et al [ 11 ], 4000 eggs were then added to each mass rearing tray, within a plastic ring floating on the water surface. Larvae were fed daily with 1% (wt/vol) IAEA diet developed and described at IAEA [ 12 ], using the feeding regime described in Soma et al [ 13 ]. Aedes aegypti larvae were reared within mass rearing trays, with a larval density of approximately 18,000 first-instar larvae (L 1 ) per tray containing 5 l of deionized water and fed with 7.5% IAEA diet (50 ml on day 1, 100 ml on day 2, 150 ml on day 3, 200 ml on day 4 and 50 ml from day 5 onwards) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%